Why Does Magnetic Resonance Imaging-Targeted Biopsy Miss Clinically Significant Cancer?. Issue 1 (26th January 2022) - Williams, Cheyenne; Ahdoot, Michael; Daneshvar, Michael A.; Hague, Christian; Wilbur, Andrew R.; Gomella, Patrick T.; Shih, Joanna; Khondakar, Nabila; Yerram, Nitin; Mehralivand, Sherif; Gurram, Sandeep; Siddiqui, Minhaj; et al.
Abstract : Purpose: Multiple studies demonstrate magnetic resonance imaging (MRI)-targeted biopsy detects more clinically significant cancer than systematic biopsy; however, some clinically significant cancers are detected by systematic biopsy only. While these events are rare, we sought to perform a retrospective analysis of these cases to ascertain the reasons that MRI-targeted biopsy missed clinically significant cancer which was subsequently detected on systematic prostate biopsy. Materials and Methods: Patients were enrolled in a prospective study comparing cancer detection rates by transrectal MRI-targeted fusion biopsy and systematic 12-core biopsy. Patients with an elevated prostate specific antigen (PSA), abnormal digital rectal examination, or imaging findings concerning for prostate cancer underwent prostate MRI and subsequent MRI-targeted and systematic biopsy in the same setting. The subset of patients with grade group (GG) ≥3 cancer found on systematic biopsy and GG ≤2 cancer (or no cancer) on MRI-targeted biopsy was classified as MRI-targeted biopsy misses. A retrospective analysis of the MRI and MRI-targeted biopsy real-time screen captures determined the cause of MRI-targeted biopsy miss. Multivariable logistic regression analysis compared baseline characteristics of patients with MRI-targeted biopsy misses to GG-matched patients whose clinically significant cancer was detected by MRI-targeted biopsy. Results: Over the study period of 2007 to 2019, 2, 103 patients met study inclusion criteria and underwent combined MRI-targeted and systematic prostate biopsies. A total of 41 (1.9%) men were classified as MRI-targeted biopsy misses. Most MRI-targeted biopsy misses were due to errors in lesion targeting (21, 51.2%), followed by MRI-invisible lesions (17, 40.5%) and MRI lesions missed by the radiologist (3, 7.1%). On logistic regression analysis, lower Prostate Imaging–Reporting and Data System (PI-RADS TM ) score was associated with having clinically significant cancer missed on MRI-targeted biopsy. Conclusions: While uncommon, most MRI-targeted biopsy misses are due to errors in lesion targeting, which highlights the importance of accurate co-registration and targeting when using software-based fusion platforms. Additionally, some patients will harbor MRI-invisible lesions which are untargetable by MRI-targeted platforms. The presence of a low PI-RADS score despite a high PSA is suggestive of harboring an MRI-invisible lesion.